Precise CRISPR/Cas9 editing of the NHE1 gene renders chickens resistant to the J subgroup of avian leukosis virus - Koslová, Anna; Trefil, Pavel; Mucksová, Jitka; Reinišová, Markéta; Plachý, Jiří; Kalina, Jiří; Kučerová, Dana; Geryk, Josef; Krchlíková, Veronika; Lejčková, Barbora; Hejnar, Jiří (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Avian leukosis virus subgroup J (ALV-J) is an important concern for the poultry industry. Replication of ALV-J depends on a functional cellular receptor, the chicken Na+/H+ exchanger type 1 (chNHE1). Tryptophan residue number 38 of chNHE1 (W38) in the extracellular portion of this molecule is a critical amino acid for virus entry. We describe a CRISPR/Cas9-mediated deletion of W38 in chicken primordial germ cells and the successful production of the gene-edited birds. The resistance to ALV-J was examined both in vitro and in vivo, and the ΔW38 homozygous chickens tested ALV-J-resistant, in contrast to ΔW38 heterozygotes and wild-type birds, which were ALV-J-susceptible. Deletion of W38 did not manifest any visible side effect. Our data clearly demonstrate the antiviral resistance conferred by precise CRISPR/Cas9 gene editing in the chicken. Furthermore, our highly efficient CRISPR/Cas9 gene editing in primordial germ cells represents a substantial addition to genotechnology in the chicken, an important food source and research model.
Keywords: zvířata; CRISPR-Cas Systems; Sodium-Hydrogen Exchanger 1; nemoci drůbeže; kur domácí; Female; Male; virus ptačí leukózy; Animals; sodíko-vodíkový výměnný transportér 1; Disease Resistance; mužské pohlaví; Chickens; ptačí proteiny; Animals, Genetically Modified; Avian Leukosis; Gene Editing; ptačí leukóza; ženské pohlaví; CRISPR-Cas systémy; Avian Leukosis Virus; Avian Proteins; editace genu; odolnost vůči nemocem; Poultry Diseases; geneticky modifikovaná zvířata